Failure Mode and Effect Analysis (FMEA) for Periodic Maintenance Tasks of Medium Voltage Switchgear 20 kV - Soetadji, Prabowo; Sutikno, Tole; Fadlil, Abdul (International Journal of Marine Engineering Innovation and Research, 2024)
Medium voltage (MV) switchgear at 20 kV, known as Panel Hubung Bagi (PHB) 20 kV in Indonesia, is a critical component of the electrical power distribution system, containing fuses, switches, and power conductors. A failure in this switchgear could lead to system-wide malfunctions, with potential catastrophic consequences such as fires or explosions. To prevent such events, it is essential to perform regular and well-planned maintenance. This research aims to optimize the maintenance process for MV switchgear, focusing on reducing maintenance tasks and frequency without compromising system reliability. The study employs the Failure Mode and Effect Analysis (FMEA) methodology, refined to reduce unnecessary maintenance actions. A Systematic Literature Review (SLR) was also conducted to analyze previous research on FMEA applications in 20 kV MV switchgear maintenance. Traditionally, maintenance was guided by manufacturers' recommendations, experience, and technical judgment, resulting in 3554 man-hours (MH) of labor every two years. However, by applying the refined FMEA process, maintenance requirements were significantly reduced to just 212 MH over the same period. This reduction represents a cost saving of 1678%, while still ensuring that the reliability of the MV switchgear at 20 kV is maintained at a high level. These findings underscore the importance of adopting systematic maintenance approaches to improve operational efficiency and reduce costs in power distribution systems.